Index to livestock literature microfiched by the ILCA/IDRC team in Kenya - Tesfai Berhane; Sirak Teklu; International Livestock Centre for Africa (Addis Ababa, Ethiopia : Documentation Services, International Livestock Centre for Africa, 1988)
The book provides information for researchers on all aspects of livestock production and related topics in sub-Sahara Africa.
Cover title: Index to livestock literature microfiched in Kenya.
Includes indexes.
"IDRC-MP/KE-1794/84."
usc 22/11/18
Loans
Keywords: Livestock; Microfiches; International Livestock Centre for Africa. Documentation Centre; Kenya